Good Corporate Governance, Sustainability Report dan Firm Value: Peran Moderasi Investment Opportunity Set - Novitasari, Maya (UMSurabaya Publishing, 2024)
This study aims to test the effect of Good Corporate Governance and Sustainability Report on Firm Value with Investment Opportunity Set as moderation. The population in this study was the LQ-45 company listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sample was taken through a purposive sampling technique totaling 45 companies with a total sample of 139. Multiple Regression Analysis Methods and Modern Regression Annalysis (MRA) using SPSS Version 25. The results of this study indicate that: (1) Managerial ownership does not affect the company value, (2 ) The Independent Board of Commissioners has no effect on company value, (3) Sustainability Report has a negative effect on company value, (4) iOS is able to moderate the effect of managerial ownership on company value, (5) iOS is able to moderate the Independent Board of Commissioners on company value, (6) IOS is able to moderate sustainability report on company value. This shows the importance of the role of iOS in GCG, Sustainability Report and Firm Value.